Hotel Essex, Atlantic Avenue, ca. 1910 - Smith and Miller (Tufts Archival Research Center, 2005)
Elevated view looking west of the Hotel Essex on Atlantic Avenue at the corner of Essex Street. People are seen on the sidewalks in the area. Automobiles and a horse-drawn vehicle are seen on Atlantic Avenue. Many of the windows have awnings. A sign for the hotel is seen over one of the entrances. 9 3/8 x 7 5/8 overall 14 x 11 Photographs